Rights of the Rohingya: effect of the Gambia vs Myanmar on Asean and Asean intergovernmental commission on human rights’ (aichr) policy and action - Mokhtar, Khairil Azmin; Rachminawati, Rachminawati (2022)
The plight of the Muslim Rohingya in Rakhine State, Myanmar has received worldwide attention, but not so much from the ASEAN. The significant action to protect the Rohingya was done upon the initiative of the OIC when adopted a unanimous resolution to bring the case to ICJ and the Gambia voluntarily represented to initiate proceedings. If other countries or regions put so much effort, why are ASEAN and its member states relatively quiet? Are there any changes of the ASEAN especially the AICHR’s policy and action after the lawsuit filed by the Gambia? This paper intends to investigate the effect of the Gambia vs. Myanmar Case on ASEAN especially the AICHR’s policy and action on the human rights protection of the Rohingya. The study adopted in this paper is qualitative legal research. The paper focuses on human rights atrocities against Rohingya which were revealed by the Court, and its update in the field. Existing ASEAN policy and action relating to the issue are also examined. The study found that the lack of protection mandate as enshrined in the AICHR’s TOR could not be claimed to justify their silence to protect Rohingya from any atrocities against them. The findings show that there was significant progress since the issuing of the ICJ’s order on the Gambia vs. Myanmar case on the policy of ASEAN especially the AICHR. The AICHR found brave enough to stand and sound their thought on the Myanmar crisis including on Rohingya. This is very significant progress the AICHR has that needs to be maintained and developed. The ICJ’s proceeding shall also be considered important in determining the future ASEAN policy towards Myanmar, especially on the issue of citizenship of the Rohingya people. In addition, it needs to influence the future human rights framework under the AICHR.